2019
DOI: 10.1016/j.omtn.2019.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated circRNA ARHGAP10 Predicts an Unfavorable Prognosis in NSCLC through Regulation of the miR-150-5p/GLUT-1 Axis

Abstract: Non-small-cell lung cancer (NSCLC) is one of the deadliest cancers in the world. Circular RNA (circRNA) has been shown to participate in oncogenesis regulation, including lung cancer. Although the involvement of circRNAs in lung cancer has been reported, the regulatory mechanisms of circRNAs in NSCLC remain poorly understood. Thus, the present study aims at investigating the role of circARHGAP10 in NSCLC progression, which has been observed to be significantly upregulated in both NSCLC tissues and cell lines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 32 publications
1
45
0
1
Order By: Relevance
“…Owing to the rapid development in high-throughput sequencing and bioinformatics, an increasing number of circRNAs have been identified as diagnostic and therapeutic targets in various malignancies 12 14 . Emerging evidence has shown that dysregulation of circRNAs plays important roles in the development and progression of colon cancer 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the rapid development in high-throughput sequencing and bioinformatics, an increasing number of circRNAs have been identified as diagnostic and therapeutic targets in various malignancies 12 14 . Emerging evidence has shown that dysregulation of circRNAs plays important roles in the development and progression of colon cancer 15 .…”
Section: Discussionmentioning
confidence: 99%
“…expression [20]. Here we found that circ_0008532 enhances the aggressiveness of BC mainly through sponging miR-155-5p and miR-330-5p.…”
Section: Discussionmentioning
confidence: 58%
“…Many reports demonstrated that abnormal circRNA expression was related to the development of a variety of human cancers, including LC [ 21 , 22 ]. A previous study claimed that circ_0001421 was up-regulated in NSCLC tissues [ 12 ]. In this research, we manifested the high expression of circ_0001421 in LC tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA SMARCA5 played an inhibition role in the progression of LC by acting as miR-19b-3p sponge [ 11 ]. Circular RNA, circ_0001421 (circ-SEC31A) was upregulated in NSCLC and its high expression predicts unfavorable prognoses [ 12 ]. However, the role of circ_0001421 in lung cancer tumorigenesis and progression was needed to be elucidated further.…”
Section: Introductionmentioning
confidence: 99%